2009
DOI: 10.1021/es8017623
|View full text |Cite
|
Sign up to set email alerts
|

Natural Organic Matter-Mediated Phase Transfer of Quantum Dots in the Aquatic Environment

Abstract: Imminent commercialization of semiconductor quantum dots (QDs) has raised concerns regarding the potential environmental impact of these materials. Understanding the partitioning behavior and obtaining information on the mobility and persistence of QDs in water is key to evaluating potential ecological hazards posed by QDs in the environment The role of natural organic matter (NOM) in the phase transfer of trioctylphosphine oxide-capped CdSe QDs from an organic solvent to water has been investigated. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 26 publications
(37 reference statements)
1
42
0
Order By: Relevance
“…Nonetheless, the raw correlation curves indicate that the average dimensions of QD-HA agglomerates were greater than those of QDs or HA alone. We previously reported similar data for TOPO-capped QDs after phase transfer into aqueous solutions of FA [46].…”
Section: Characterization Of Phase-transferred Qdssupporting
confidence: 67%
See 1 more Smart Citation
“…Nonetheless, the raw correlation curves indicate that the average dimensions of QD-HA agglomerates were greater than those of QDs or HA alone. We previously reported similar data for TOPO-capped QDs after phase transfer into aqueous solutions of FA [46].…”
Section: Characterization Of Phase-transferred Qdssupporting
confidence: 67%
“…We recently reported that CdSe QDs capped with TOPO were transferred efficiently from hexane into aqueous solutions of humic acid (HA) or fulvic acid (FA) [46]. After phase transfer, QDs were present within agglomerates of HA or FA.…”
Section: Introductionmentioning
confidence: 99%
“…Possibilities (i) and (ii) could arise if the polymer degrades to produce hydrophobic debris that adheres to the bulk optic, and the debris transports to the filtrate only in the presence of NOM that acts as a surfactant. In a related observation, Navarro et al 30 reported that NOM facilitated phase transfer of organic ligand capped CdSe QDs from organic solvent to the water phase. Here we used UV-vis and fluorescence spectrometry to look for suspended QDs in the filtrates but could not detect any spectral features characteristic of QDs.…”
Section: Resultsmentioning
confidence: 94%
“…Steric repulsive forces result from adsorbed polymers or surfactants used to modify NP surfaces or the adsorption of NOM in aquatic environments and prevent particles from coming into the close contact required for aggregation. When sterically stabilised particles approach each other, the interactions between the large chain-like adsorbed molecules cause repulsion due to an increasing number of chain-chain interactions at the expense of more favourable chain-solvent interactions [51]. Hydration forces arise in the case of nanoparticles modified with hydrophilic molecules which may have significant amounts of bound water; an additional repulsive force occurs hindering the approach of the two hydrated surfaces as those water molecules must be displaced for the particles to come into contact [52].…”
Section: Measurement Of Zeta Potential and Particle Size Analysismentioning
confidence: 99%